Biobased and environmental benign coatings - Tiwari, Atul; Galanis, Anthony; Soucek, Mark D. (Materials Degradation and Failure., 2016)
This book will have the recent information on the developments in the emerging field of environmental-friendly coatings. Crucial aspects associtaed with coating research will be presented in form of the indivudual chapters. Close attention will be paid to include essential aspects that are necessary to understand the porperties and applications of the novel materials. Different methods and techniques of synthesis and charcaterization will be detailed as individual chapters. It will also discuss the characterization techniques used in the area of such coatings. there will be chapters that descirbe the current status and future prospects. The topics will be selected so they are easy to understand and useful to new scholars as well as advanced learners. No book has been written on this subject so far.